Comparison of Toric and Spherical Orthokeratology Lenses in Patients with Astigmatism - Jun Jiang; Lili Lian; Feifu Wang; Ling Zhou; Xuhong Zhang; E. Song (Journal of Ophthalmology)
Purpose. This retrospective study aimed at comparing the efficacy and safety of toric and spherical orthokeratology lenses in the treatment of patients with moderate to high astigmatism. Methods. Fifty adolescents with myopia and moderate to high astigmatism (≥1.50 D) who underwent consecutive orthokeratology treatment for at least 1 year were included in this study. The toric group comprised 25 subjects (25 eyes, 11 M, 14 F; age, 10.67 ± 1.46 years) who were fitted with toric orthokeratology lenses. The spherical group comprised 25 subjects (25 subjects, 11 M, 14 F; age, 11.45 ± 1.63 years) who were fitted with traditional spherical orthokeratology lenses as a control. Corneal topography, visual acuity, axial length, and slit-lamp examinations were performed to determine the differences between these two groups. The corneal tangential difference mapping was conducted between baseline and every subsequent visit to calculate the magnitude of lens decentration. The corrective effect of ortho-K lens was measured by using the corneal axial difference map. Results. The mean decentration and its vertical vector were significantly less in the toric group than in the spherical group after 1 month of lens wear. In toric group, the corneal astigmatism decreased from 1.85 ± 0.31 D at baseline to 1.45 ± 0.85 D after the first month of wear. There was a significant linear correlation between the change in corneal astigmatism and lens decentration in the toric group from 1 month to 1 year (Y = 3.268 ∗ X + 0.9182, R2 = 0.5035, p<0.0001 (X: lens decentration; Y: astigmatic changes)). There were no significant differences in the post-OK uncorrected visual acuity, myopia control, or ocular health between the toric and spherical groups. Conclusion. The toric orthokeratology lens design can effectively reduce the lens decentration magnitude and CJ180 from 1-month visit to 12-month visit of patients with high or moderate corneal astigmatism. Meanwhile, there was no significant difference in visual acuity, myopia control, and ocular health throughout 12 months. However, the effect of toric lenses on corneal morphology may be susceptible to lens positioning.